The Students’ Difficulties In Speaking English at Eleventh Grade Of PPTQ Muallimin Muhammadiyah Pakan Sinayan - Indria Nofitri; Syahrul Syahrul; Eliza Eliza; Hilma Pami Putri (Al-Afkar: Jurnal Pemikiran dan Pendidikan Islam, 2026)
This research was done related to the problem that happen at most the eleventh grade students at PPTQ Mu’allimin Muhammadiyah Pakan Sinayan. The problem was most of students difficult to practice speaking English in front of the class. In addition the students were too shy to make permission by using English and speak with friends that reflexively would laughed to them if they make a mistake. Furthermore, this research is conducted to described that factor affecting of the students’ difficulties in speaking English at Eleventh grade of PPTQ Mu’allimin Muhammadiyah Pakan Sinayan. The type of the research was descriptive qualitative approach. The data was collected from the interview to the informants. The source of the research was the eleventh grade students, the informant based on the teacher who determines the students who have problems. The technique of data analysis used Miles and Huberman’ Model, consisted of : data collection, data reduction, display the data, and conclusion. Based on analysis of the data, it was found that the factor affecting of students’ difficulties in speaking English are lack of vocabulary, lack of competence in writing sentences, when the students perform speaking English they are nervous and stutter in expressing the sentences, lack ideas to create and develop the sentences, and lack of interest in learning English. The main factor affecting of the students’ difficulties are lack of interest in learning English. In addition, they are given a few minutes to understand the topic that is given by the teacher, and suggest them to the English media that have the easier vocabularies to be understood by the students.